¿Menos oportunidades en la legalidad conducen a la ilegalidad? un análisis para el caso colombiano (2020)
This paper studies the relation between unemployment rate and robbery rate for Colombiaþs 23 main cities categorized by DANE from 2010 to 2016. Through diverse fixed effects model estimations and contrasting results with an instrumental variable approach to solve endogeneity problems, the results identify that unemployment rate variations do not affect directly variations of robbery rates for the 23 cities studied. Additionally, it was found that higher population levels are correlated to higher robbery rates.